Endodontic management of C-shaped canals: A case series - K. B. Salah; H. Boukhris; H. Zidani; I. Gnaba; S. B. Youssef (Эндодонтия Today)
INTRODUCTION. C-shaped root canals represent a complex anatomical variation, primarily seen in mandibular molars. Their intricate morphology poses significant challenges for diagnosis, cleaning, shaping, and obturation in endodontic practice.AIM. To present a series of clinical cases illustrating the diagnosis and endodontic management of different types of C-shaped canals based on Fan’s classification.MATERIALS AND METHODS. Four clinical cases involving mandibular molars with C-shaped canal configurations were managed in accordance with CARE and PRICE guidelines. Each case included clinical and radiographic diagnosis, working length determination, cleaning and shaping with either the R2 Reciproc (VDW) or PlexV (Orodeka) system, irrigation with NaOCl and EDTA under ultrasonic activation, and obturation using thermocompaction or single-cone techniques with bioceramic sealers.RESULTS. All cases demonstrated successful identification and management of C-shaped canal systems (types C1 to C4). Clinical and radiological follow-up at 1 and 3 months showed favorable healing with resolution of symptoms and periapical pathology.CONCLUSIONS. Early and accurate diagnosis of C-shaped canals, supported by clinical and radiographic examination, is critical for successful endodontic outcomes. The use of magnification, appropriate canal preparation techniques, and bioceramic materials significantly enhances treatment success in such complex anatomical variations.